Increase of perfect orders through the application of mixed methodologies in a company in the heavy freight transportation sector - Cusihuaman Torres, Luis Alonso (2024)
The heavy freight transportation sector is projected to grow by 12% annually, increasing the need to address the demand generated by the economic growth in Peru, particularly from related sectors such as trade and logistics. This article focuses on freight transportation services and the challenges it faces. Therefore, a study was conducted on the process from the arrival of requests to the dispatch of cargo, and BPM, 5S, and Route Planning were proposed to improve the Perfect Order indicator, which was found to be 76.10% due to poor information management and a lack of process improvement planning. After implementing the pilot plan and simulating it using Arena software version 16.1, it was demonstrated that the proposed model improvement increased the Perfect Order indicator to 95%.